Correlation Among Anatomic Landmarks, Location of Subthalamic Deep Brain Stimulation Electrodes, Stimulation Parameters, and Side Effects During Programming Monopolar Review. Issue 2 (March 2015) - Matias, Caio M.; Mehanna, Raja; Cooper, Scott E.; Amit, Amit; Lempka, Scott F.; Silva, Danilo; Carlotti, Carlos G.; Butler, Robert S.; Machado, Andre G.
Abstract : BACKGROUND: Clinical benefits of deep brain stimulation can be limited by the presence of side effects produced by current spread to adjacent structures. OBJECTIVE: To identify a correlation between coordinates for each individual contact, neighboring structures, and pattern of side effects. METHODS: Coordinates of the electrodes and anatomic landmarks were obtained with a stereotactic surgical planning software and were correlated with stimulation-related side effects by using univariate and multivariable analyses. RESULTS: Monopolar stimulation elicited capsular side effects (CSEs) in 208 of 316 contacts (65.8%) and noncapsular side effects (NCSEs) in 223 of 316 contacts (70.6%). The occurrence of CSEs was correlated with contact number ( P = .009) and with the "Z" ( P = .03), whereas voltage threshold to CSEs exhibited correlation with the internal capsule angle ( P = .035). The occurrence of NCSEs was correlated with contact number ( P = .005), "X" ( P = .03), "Y" ( P = .004), and the distance to the red nucleus ( P = .001 and P = .003). There was correlation between voltage threshold to NCSEs and the internal capsule angle ( P = .006), electrode's coronal angle ( P = .02), "X" ( P = .001), "Y" ( P < .001), "Z" ( P < .001), and the distances to the internal capsule ( P = .02) and to the red nucleus ( P = .004 and P < .001). CONCLUSION: A better understanding how patient anatomy, stimulation parameters, and lead location in relation to neighboring structures influence the occurrence of side effects can be useful to inform targeting strategies. ABBREVIATIONS: AC, anterior commissure CSE, capsular side effect DBS, deep brain stimulation IC, internal capsule MCP, midcommissural point NCSE, noncapsular side effect PC, posterior commissure PD, Parkinson disease PW, pulse width STN, subthalamic nucleus